A influência da intervenção implementada por pais sobre as habilidades sociocomunicativas de crianças com Transtorno do Espectro Autista: uma abordagem formativa e centrada na família - Oliveira, Jéssica Jaíne Marques de (2023)
Autism Spectrum Disorder (ASD) is characterized by deficits in the sociocommunicative and behavioral dimensions, highlighting the importance of early diagnosis and intervention. In recent decades, it has been possible to see the importance of interventions that focus on the family as a predictor of benefits for their child in the intervention process. Parent-Initiated Intervention (PII) has been highlighted as an evidence-based practice (EBP) for people with ASD. The aim of this study was to analyze the effects of PBI on the sociocommunicative skills of children with ASD, based on the training of consultants and parents in the school context. This is an interventional study using a Mixed Methods approach, combining quantitative and qualitative methods. The participants were a special education teacher (consultant), three families (one father and two mothers) and their children with ASD, who attended a regular municipal nursery school. Initially, the consultant underwent training on IIP, in which learning transfer was measured pre- and post-test. Then a quasi-experimental within-subjects study investigated the effect of parents' mediating behaviors (independent variable) on their children's sociocommunicative skills (dependent variable), complemented by statistical analysis of the effect size (Tau-U). The results showed that there was a general transfer of learning (45%) about PII in the consultant training. The study's fidelity index was 100%, based on the application of the fidelity checklist throughout the PII process. In addition, the results showed that the IIP produced a statistically significant effect (Tau-U=0.6735) on the children's sociocommunicative skills, showing improvements in the categories of verbal and non-verbal shared attention and affective contact, by an increase in behaviors such as: responses with words, exclamatory comments, pointing, imitating, smiling, expressions of questions, among others. Parents also increased their mediating behaviors in the redirection and encouragement classes (verbal commands, prompts, motivators and feedbacks). Finally, the social validity of the study showed that the PII is effective for replication in other contexts and that it contributes to the acquisition of skills by parents in managing their children, increasing the children's sociocommunicative skills and also strengthening the relationship between parents and their children. The novelty of this study stands out, as it was applied in a school context and provided easy access for families. It is suggested that in order to replicate this research, the uniqueness of each family should be taken into account and the necessary adaptations made for each context. In addition, IIP can be implemented via specialized educational service in schools, taking into account family demands and the benefits provided to students.